2020
DOI: 10.20944/preprints202008.0488.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Renewable Energy Startups and SME

Abstract: India’s energy needs are in demand with the increase in energy and other electric uses which is highest among the world. There are sectors which heavily rely on energy generated by fossil fuels but there is also seen a paradigm shift towards renewable energy sources. If India continues to rely on the former then they end up blocking development in energy system meeting uncertainties and face difficulties in supply of fossil fuels. To meet the fast-growing economy, India needs to supply the energy 3-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, they could help by obtaining better resources such as appropriate skillsets, external information, customer data, access to suppliers and so on while maintaining appropriate ethical and moral guidelines (Hillman et al , 2000). Several studies have observed that organizations that adopt blockchain technology impact them to act ethically and morally, and their actions are consistent with the appropriate governance model (Goel, 2015; Iansiti and Lakhani, 2017; Yermack, 2017). Thus, it is argued that adoption of blockchain technology could create value for organizations, leading them toward the betterment of the organization–society–environment interface and impacting organizations’ sustainability.…”
Section: Literature Review and Theoriesmentioning
confidence: 92%
“…For example, they could help by obtaining better resources such as appropriate skillsets, external information, customer data, access to suppliers and so on while maintaining appropriate ethical and moral guidelines (Hillman et al , 2000). Several studies have observed that organizations that adopt blockchain technology impact them to act ethically and morally, and their actions are consistent with the appropriate governance model (Goel, 2015; Iansiti and Lakhani, 2017; Yermack, 2017). Thus, it is argued that adoption of blockchain technology could create value for organizations, leading them toward the betterment of the organization–society–environment interface and impacting organizations’ sustainability.…”
Section: Literature Review and Theoriesmentioning
confidence: 92%
“…In other words, a significant number of important industries can contribute to business sustainability using disruptive technologies, but they must update their business models to achieve a better positive impact on society, the environment, and the economy. (Goel, 2015) It optimizes costs to become efficient and can be linked to the waste design of the circular economy posed by Ellen MacArthur.…”
Section: E-commercementioning
confidence: 99%